A Haunting On The Hill - Hand, Elizabeth (New York, NY : Mulholland Books / Little, Brown and Company, 2023)
"Open the door....Holly Sherwin has been a struggling playwright for years, but now, after receiving a grant to develop her play Witching Night, she may finally be close to her big break. All she needs is time and space to bring her vision to life. When she stumbles across Hill House on a weekend getaway upstate, she is immediately taken in by the mansion, nearly hidden outside a remote village. It's enormous, old, and ever-so eerie--the perfect place to develop and rehearse her play. Despite her own hesitations, Holly's girlfriend, Nisa, agrees to join Holly in renting the house for a month, and soon a troupe of actors, each with ghosts of their own, arrive. Yet as they settle in, the house's peculiarities are made known: strange creatures stalk the grounds, disturbing sounds echo throughout the halls, and time itself seems to shift. All too soon, Holly and her friends find themselves at odds not just with one another, but with the house itself. It seems something has been waiting in Hill House all these years, and it no longer intends to walk alone ..." --.
new book 2024 winter.
Keywords: Haunted houses -- Fiction; Women dramatists -- Fiction; Actors -- Fiction; Horror; Drama; Psychological fiction; Theater. -- Production and direction -- Fiction; Psychological fiction; Thriller fiction; Ghost stories; Horror fiction